Analysis of the Cultural Landscape Elements in the Municipality of Bistrița and Their Potential for Tourism Valorization - VASILIȚĂ-CRĂCIUN, Ileana-Cristina (Studia Universitatis Babeș-Bolyai Geographia, 2023)
The study of the cultural landscape elements in the urban area of Bistrița determines clear tourist values that refer to the attractiveness of both natural elements and that of cultural ones. This study highlights the specific natural environment, the churches and other buildings that have a characteristic function, belonging to different historical periods, starting from the Middle Ages. All of these benefit from an appropriate infrastructure that favors tourist access and capitalization, currently to a modest extent, but which as a whole can constitute the basis of a new integrated development strategy of the city. Thus, the study reveals both the analysis of the elements with real tourist values, as well as the main objectives to be achieved for the subsequent development of the area.